Engineered Potato virus X nanoparticles support hydroxyapatite nucleation for improved bone tissue replacement. (15th October 2017) - Lauria, Ines; Dickmeis, Christina; Röder, Juliane; Beckers, Malin; Rütten, Stephan; Lin, Ying Ying; Commandeur, Ulrich; Fischer, Horst
Graphical abstract: Abstract: Bionanoparticles based on filamentous phages or flexuous viruses are interesting candidates for meeting the challenges of tailoring biomineralization in hydrogel-based bone tissue substitutes. We hypothesized that hydroxyapatite crystal nucleation and matrix mineralization can be significantly increased by mineralization-inducing (MIP) and integrin binding motif (RGD) peptides presented on biomimetic nanoparticles. In this study, Potato virus X (PVX), a flexible rod-shaped plant virus was genetically engineered to present these functional peptides on its particle surface. Recombinant PVX-MIP/RGD particles were isolated from infected Nicotiana benthamiana plants and characterized by western blot, SEM, TEM, and TPLSM in MSC cultures. The presence of RGD was proven by cell attachment, spreading, and vinculin cluster analysis, and MIP by in vitro mineralization and osteogenic differentiation assays. Thus the tailored surface of genetically engineered PVX forms fibril-like nanostructures which enables enhanced focal adhesion-dependent cell adhesion, and matrix mineralization verified by Alizarin. Hydroxyapatite crystal nucleation is supported on recombinant PVX particles leading to a biomimetic network and bundle-like structures similar to mineralized collagen fibrils. In conclusion, the recombinant flexuous PVX nanoparticles exhibit properties with great potential for bone tissue substitutes. Statement of Significance: A suitable biomaterial for tissue engineering should be able to mimic the endogenous extracellular matrix by presenting biochemical and biophysical cues. Novel hydrogel-based materials seek to meet the criteria of cytocompatibility, biodegradability, printability, and crosslinkability under mild conditions. However, a majority of existing hydrogels lack cell-interactive motifs, which are crucial to modulate cellular responses. The incorporation of the plant virus PVX to the hydrogel could improve functions like integrin-binding and mineralization due to peptide-presentation on the particle surface. The tailored surface of genetically engineered PVX forms fibril-like nanostructures which enables enhanced focal adhesion-dependent cell adhesion and matrix mineralization and offers great potential for the development of new hydrogel compositions for bone tissue substitutes.